2006
DOI: 10.1080/14622200500264432
|View full text |Cite
|
Sign up to set email alerts
|

Social class, education, and smoking cessation: Long‐term follow‐up of patients treated at a smoking cessation unit

Abstract: Our objective was to examine social class and educational differences in long-term smoking cessation success among a cohort of smokers attending a specialized smoking clinic. We studied sustained abstinence after cessation among 1,516 smokers (895 men and 621 women) treated for smoking cessation between 1995 and 2001 at a university teaching hospital in the metropolitan area of Barcelona, Spain. We calculated 1-year and long-term (up to 8-year) abstinence probabilities by means of Kaplan-Meier curves and the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
55
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 42 publications
14
55
1
4
Order By: Relevance
“…The authors' results are similar to those reported in other studies, and they found no difference [7,8]. In the present study, females smoked less cig/day than males (23.7 cig/day vs. 30.3 cig/day, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…The authors' results are similar to those reported in other studies, and they found no difference [7,8]. In the present study, females smoked less cig/day than males (23.7 cig/day vs. 30.3 cig/day, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Although we do not expect that the outcome of an attempt would influence memories of how it took place or that such memories would be influenced by the factors we have studied here, we cannot rule out these possibilities. Furthermore, we cannot rule out recall bias being a plausible explanation, at least in part, for the lower report of abrupt quitting among the socially disadvantaged since this group is more likely to have shorter or brief attempts (Fernandez et al, 2006), which are more easily forgotten. Another limitation might be the variation in understanding of what constitutes abrupt cessation.…”
Section: Discussionmentioning
confidence: 95%
“…Greater use of cutting down might be a reason why smokers from more disadvantaged socioeconomic backgrounds are sometimes found to have less success in quitting (Fernandez et al, 2006;West et al) and why sometimes females are found to be less successful than males (Bjornson et al, 1995;Wetter et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Educational level is stable in adults, while the occupation variable can show considerable instability over the course of life (Belleudi et al, 2006), which would explain why the former yields greater significance and more robust results than the latter, as the previously-cited studies have also shown (Fernández et al, 2006;Yanez, Leiva, Gorreto, Estela, Tejera, & Torrent, 2013).…”
Section: Discussionmentioning
confidence: 99%